Loch Ness. Series 1 [videorecording (DVD)] - Fraser, Laura, 1976-; Finneran, Siobhan, 1967-; Ash, William, 1977-; Bannon, Jack, 1940-2017 (Acorn, 2017)
Against the stunning landscapes of Scotland's iconic Loch Ness, local detective sergeant, Annie Redford finds herself in the midst of her first murder investigation; DCI Lauren Quigley is called in to lead the investigation, joined by forensic psychologist Blake Albrighton who believes there is more to the murder than initially meets the eye. Grief, terror, and suspicion soon shatter the town's normality.